IMAGING OF ASEISMIC FAULT SLIP TRANSIENTS RECORDED BY DENSE GEODETIC NETWORKS - McGuire J.J.; Segall P. (My University, 2003)
The large-scale continuous GPS networks that have emerged in the last decade have documented a wide-range of aseismic deformation transients that resulted from physical processes such as aseismic fault slip and magma intrusion. In particular, a new class of (M ~ 7) slow earthquakes with durations ranging from days to months have been observed with GPS arrays located above the downdip portion of subduction zone thrust interfaces. Interpretation of the displacement time-series resulting from these events is not straightforward owing to the contaminating effects of multiple contributing signals such as fault-slip, local benchmark motion, seasonal effects, and reference frame errors. We have developed a time-dependent inversion algorithm based on the extended Kalman filter which can separate the various signals and allow the space-time evolution of these slow-slip transients to be studied in detail. We applied the inversion algorithm to the 1999 Cascadia slow earthquake. This event had two primary episodes of moment-release separated by a two week period in which relatively little moment-release occurred. The Cascadia event and other slow earthquakes share numerous similarities with both ordinary earthquakes and afterslip transients suggesting that they may represent fault slip under a conditionally stable regime.
Keywords: aseismic fault slip; geodetic networks; slow earthquakes